Collaborative Integration of Bioinformatics Knowledge Management System and Mobile Wireless Devices - Alomary, Fahad Omar (Transactions on Engineering and Computing Sciences, 2019)
Knowledge Management System (KMS) currently becomes a common medium to distribute knowledge by using the Information Technology (IT) as enabler tools for everyone to reach, share with among the members, and used it from any workplace in the world at any time. In the context of bioinformatics community of practice (CoP) is also has opportunities to leverage and share their knowledge with collaborative technology to create, gather, access, organize, distribute and disseminate the knowledge among them for various purposes such as learning process, research and development (R&D) and others. This paper describes on the theoretical concepts and approach of integrating mobile wireless devices into Bioinformatics KMS that could be implemented in institution by demonstrating on how the framework of KMS model that is developed using relevance software. The achievement of conducting mobile wireless devices into Bioinformatics KMS framework is an added value for the CoP in the institution that needs to implement the Bioinformatics KMS, which can help them to achieve their aims and mission statements. The emphasis also will be given to the activities for each stage in the KM life cycle including the critical success factor (CSF) in order to make sure that Bioinformatics KMS initiatives will deliver competitive advantage to the CoP in the institutions.